Ecofeminism in Indonesian Environmental Law: Gender Equality for Sustainable Natural Resource Management - Prasetyo, Eko (SPECTRUM: Journal of Gender and Children Studies, 2024)
This paper explores the intersection of gender equality and sustainable natural resource management in Indonesia, utilizing ecofeminism as a theoretical framework. It examines the significant yet underappreciated role of women in environmental stewardship, particularly within rural and indigenous communities, and how current environmental policies fail to fully integrate their contributions. The study analyzes the limitations of Indonesian environmental law in promoting gender-inclusive policies, highlighting structural barriers, patriarchal systems, and ineffective policy implementation. Additionally, the potential of ecofeminism to enhance both gender equality and environmental justice is discussed, offering recommendations for more inclusive and sustainable natural resource management. The research suggests that empowering women and incorporating their local knowledge is essential for achieving long-term environmental sustainability and social justice in Indonesia.